Role of diet and dietary habits in causing dental caries among adults reporting to a tertiary care hospital in Pakistan; a case-control study - Kiran Javed; Muhammad Zubair Nasir; Maham Jalees; Manzoor Ahmed Manzoor (Heliyon, 2023)
Objective: To determine the association of diet and dietary practices with dental caries among adults. Design: A case-control study. Setting: Operative Department, Rawal Institute of Health Sciences, Islamabad, Pakistan. Participants: 300 participants of both genders, aged 25–50 years. Interventions: A food frequency questionnaire and a patient proforma were used to determine the frequency and preferences of diet and dietary habits that may be associated with dental caries among adults, respectively. The diet and dietary habits of 150 adults with caries (cases) were compared with those of 150 adults without dental caries (control). An independent sample T-test was applied to determine the difference in mean age. Mann-Whitney and Chi-Square tests were applied to determine the significance of diet and dietary habits respectively. Multivariate logistic regression analysis determined the odd ratio change in significant variables. P-value ≤0.05 was considered significant. Results: Refined sugar (p-value = 0.69), fruit juices (p-value = 0.45), carbonated beverages (p-value = 0.91), duration of consumption of sugary food (p-value = 0.07), and frequency of brushing (p-value = 0.15) were not found to be significantly associated with dental caries in adults. The gender (p-value = 0.02), preferred time for eating sugary foods (p-value <0.001), smoking (p-value <0.001), and tea consumption (p-value = 0.02) were found to be significantly associated with dental caries. Conclusion: Adults who regularly consumed sugar as a snack other than regular mealtimes were more likely to be associated with dental caries. Men, smokers, and adults who frequently took shots of sugar with their tea were more likely to be associated with dental caries.